What motivates firms from emerging economies to go internationalization? - Zeng, Ruochen; Zeng, Saixing; Xie, Xuemei; Tam, Chiming; Wan, Tianwei (Technological and Economic Development of Economy, 2012)
With advent of economic globalization, internationalization has become one of the most important strategies for firms to achieve sustainable growth. Based on the empirical research in the Yangtze River Delta region in China, the method of Correspondence Analysis was employed to study the motivations for going internationalization of Chinese enterprises. The main findings include: (1) the motivations for internationalization of enterprises depend on their scale, and largesized enterprises are mainly motivated by the purpose of creating global brands and enhancing domestic reputation; (2) the ownership of enterprises has obvious influence on their motivations for going internationalization, and (3) enterprises in different industries also show different levels of motivation for internationalization.